2008
DOI: 10.1002/ar.20679
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Development and Differentiation During Human Liver Organogenesis

Abstract: The vascular architecture of the human liver is established at the end of a complex embryological history. The hepatic primordium emerges at the 4th week and is in contact with two major venous systems of the fetal circulation: the vitelline veins and the umbilical veins. The fetal architecture of the afferent venous circulation of the liver is acquired between the 4th and the 6th week. At the end of this process, the portal vein is formed from several distinct segments of the vitelline veins; the portal sinus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(130 citation statements)
references
References 50 publications
2
127
0
1
Order By: Relevance
“…In the present study, three HVs were observed in 68.4% of the cases after CS15, indicating that the three HVs are acquired around CS15 in most cases. These data are consistent with those of a previous study reporting profound remodeling of the efferent venous system during the 5th gestational week (Dickson, 1957;Collardeau-Frachon and Scoazec, 2008). Three HVs were not identified until after CS17 in 19.6% of cases, suggesting that there are several individual variations in the number and arrangement of the terminal HVs, in contrast to the afferent venous circulation systems.…”
Section: The Morphology and Morphometry Of Embryonic Liversupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, three HVs were observed in 68.4% of the cases after CS15, indicating that the three HVs are acquired around CS15 in most cases. These data are consistent with those of a previous study reporting profound remodeling of the efferent venous system during the 5th gestational week (Dickson, 1957;Collardeau-Frachon and Scoazec, 2008). Three HVs were not identified until after CS17 in 19.6% of cases, suggesting that there are several individual variations in the number and arrangement of the terminal HVs, in contrast to the afferent venous circulation systems.…”
Section: The Morphology and Morphometry Of Embryonic Liversupporting
confidence: 92%
“…Original and first-hand data regarding the stages of development of the vascular architecture of the liver are scarce (Collardeau-Frachon and Scoazec, 2008). Though the asymmetry of the hepatic vascular structure may be acquired between CS13 and CS16, the precise stages of development could not be determined.…”
Section: The Morphology and Morphometry Of Embryonic Livermentioning
confidence: 99%
See 1 more Smart Citation
“…The observed abnormalities are in line with the expression pattern of Plexin-B2 in the highly specialized discontinuous endothelium of the liver. During both development and liver regeneration in the adult, the hepatic portal veins and sinusoids derive from preexisting vessels through angiogenesis (54,55). There is evidence that RhoA activation downstream of Plexin-B1 stimulates cellular processes in endothelial cells that are crucial for angiogenesis, including chemotactic migration and tubulogenesis (56).…”
Section: Discussionmentioning
confidence: 99%
“…This venous system transports the splanchnic venous flow through the portal vein to the liver [1,6]. The afferent venous circulation of the liver as well as its efferent venous system, i.e., the hepatic veins, derives from an extraembryonic venous system, the vitelline venous system, which transports blood from the yolk sac to the heart at the end of the 3rd week of gestation [7]. This extraembryonic origin of the portal system perhaps determines some of the pathological evolutive characteristics when it suffers hyperpressure.…”
Section: Introductionmentioning
confidence: 99%